Habituation of Local Culture in Order to Prevent Religious Radicalism in Sukoharjo, Central Java - Ahmad Sihabul Millah; Yuni Ma’rufah; Khoirul Imam (UIN Sunan Kalijaga Yogyakarta, 2018)
This article is intended to see the response of a group of Sukoharjo people related to their effort in prevention of radicalism through local cultural habituation. A group of people who joined into Sanggar Sekar Jagad in Bakalan Sukoharjo Village try to find a way out by way of rejuvenate local culture and traditional art that began to be abandoned by society. Using case study method through empirical investigation by means of data collecting through interview, observation, and documentation, it is expected to be able to answer how the practice of local cultural habituation developed by Sanggar Sekar Jagad society in order to prevent religious radicalism in the region was, and what factors which underlied the practice.[Artikel ini bertujuan untuk melihat respons sekelompok masyarakat Sukoharjo berkaitan dengan upaya mereka dalam mencegah radikalisme melalui habituasi budaya lokal. Sekelompok masyarakat yang tergabung dalam Sanggar Sekar Jagad di Desa Bakalan Sukoharjo mencoba mencari jalan keluar dengan cara menghidupakan kembali budaya lokal dan kesenian tradisional yang mulai ditinggalkan oleh masyarakat. Dengan menggunakan metode studi kasus, melalui penyelidikan empiris, dengan cara mengumpulkan data wawancara, observasi, dan dokumentasi, diharapkan mampu memberi jawaban tentang bagaimanakah praktik habituasi budaya lokal yang dikembangkan masyarakat Sanggar Sekar Jagad dalam rangka mencegah radikalisme agama di wilayah itu, dan faktor apa sajakah yang melatari praktik tersebut.]